2018
DOI: 10.1200/jop.2017.028191
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Potentially Preventable Cancer- and Chronic Disease–Related Emergency Department Use in the Year After Treatment Initiation: A Regional Study

Abstract: The prevalence of potentially preventable ED visits was generally high, but varied depending on the diagnosis code fields and the group of codes considered. Future research is needed to understand the complex landscape of potentially preventable ED visits and measures to improve value in cancer care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 19 publications
2
95
1
2
Order By: Relevance
“…We have identified a need for improved symptom control before and during the ED visit. Pain is a driver of ED presentation among patients with cancer, 4 , 12 and appropriately managing pain is a significant contributor to improving quality of life in these patients. 25 , 26 Pain in the ED was present in 62.1% of study participants, whereas 249 (23.2%; 95% CI, 20.7%-25.8%) had no pain assessment documented in the ED medical record.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified a need for improved symptom control before and during the ED visit. Pain is a driver of ED presentation among patients with cancer, 4 , 12 and appropriately managing pain is a significant contributor to improving quality of life in these patients. 25 , 26 Pain in the ED was present in 62.1% of study participants, whereas 249 (23.2%; 95% CI, 20.7%-25.8%) had no pain assessment documented in the ED medical record.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of visits by patients with cancer to the ED found that nearly one half were associated with potentially preventable diagnoses. 42 In addition, medical home models, patient navigation, and related interventions to improve outpatient support (eg, community-based palliative care, after-hours telephone support, evidence-based treatment guidelines, out-ofhospital emergency teams) have been shown to address patients' urgent needs while reducing acute care use and improving quality of care. [43][44][45] One oncology practice found that implementing an oncology nurse practitioner-led supportive care clinic to address urgent care needs reduced symptom-related care admissions by 31%.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of high-risk patients may direct supportive care and prevent such events, 2 and it has been estimated that approximately half of ED visits during cancer therapy are potentially preventable. 7 A recent literature review recommended identification of high-risk patients as a best practice to direct interventions and resources to reduce unplanned acute care for patients with cancer. 6 Given the predictive complexity of this actionable, unmet clinical need, there is an opportunity to leverage artificial intelligence and machine learning (ML), which has recently demonstrated successes in many areas of medicine.…”
Section: Introductionmentioning
confidence: 99%